2011
DOI: 10.1021/cg200245m
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Gas Composition in the Mother Liquor on the Formation of Macroscopic Inclusions and Crystal Growth Rates. Case Study with Ciclopirox Crystals

Abstract: A homemade setup was designed in order to investigate the influence of gas bubbling on the crystal growth of the active pharmaceutical ingredient ciclopirox. It appears from these experiments performed in stagnant and isothermal conditions that gases containing oxygen atoms (air, dioxygen, nitrous oxide, and carbon dioxide) lead to high crystal growth rates and promote the formation of liquid inclusions whereas gases free from oxygen (nitrogen, helium, argon, dihydrogen), as well as degassing treatments, cause… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
34
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 27 publications
(42 citation statements)
references
References 17 publications
5
34
0
Order By: Relevance
“…There is a dramatic decrease in growth rate from the degassed solutions to the other four, gas‐saturated solutions. Waldschmidt et al 13 concluded that, in the case of ciclopirox, crystals can be free from macroscopic inclusion when using degassed solutions or solutions saturated with non‐oxygen‐containing gases. Contrary to this phenomenon, the experimental results of Seidel and Ulrich 14 showed that lowering the gas content as much as possible by degassing resulted in an increase in cavity size by up to 50 % in the system of salicylic acid, indicating that the gas content in the solutions has a negative influence on the formation of cavities.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There is a dramatic decrease in growth rate from the degassed solutions to the other four, gas‐saturated solutions. Waldschmidt et al 13 concluded that, in the case of ciclopirox, crystals can be free from macroscopic inclusion when using degassed solutions or solutions saturated with non‐oxygen‐containing gases. Contrary to this phenomenon, the experimental results of Seidel and Ulrich 14 showed that lowering the gas content as much as possible by degassing resulted in an increase in cavity size by up to 50 % in the system of salicylic acid, indicating that the gas content in the solutions has a negative influence on the formation of cavities.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, it can be deduced that, e.g., when CO 2 is dissolved in a solution, the solute shows a high potential to change the solubility. Besides that, dissolved gases have a vital effect on the formation of cavities or mother liquid inclusions, leading to an increased impurity of the product 13, 14. Therefore, trace amounts of dissolved gases could also be regarded as one type of impurities that should not be underestimated.…”
Section: Introductionmentioning
confidence: 99%
“…But cavity‐ respectively inclusion‐containing crystals are not only formed by such a phase transformation. They are also described to appear, e.g., during cooling crystallization, evaporative crystallization, or additive‐induced precipitation from solution 4–6. The mechanism of this phenomenon is explained by inhibited diffusion and mass transport during crystal growth 6.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the center part of a crystal face is not able to grow, which leads to the formation of inclusions. The inhibition of diffusion and mass transport is discussed to be caused or intensified by impurities or even nano or micro gas bubbles in the solutions 4, 6, 7.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation